Two new species of the spider genus Antoonops (Araneae: Oonopidae), with a key to the known species - Fannes, Wouter (Zootaxa, 2013)
Two new species of the goblin spider genus Antoonops are described, bringing the total number of species to six. Antoonops kamieli sp. nov. is described from two males and one female collected in Bouaké, Ivory Coast. The species can be easily distinguished from congeners by its large eyes. In addition, the males are characterized by a distinct depression on the ventral abdomen. Antoonops sarae sp. nov. is described from four females collected in Tchabal Mbabo, Cameroon. The species is unusual in having a long postepigastric scutum and a genital duct with finger-like protrusions. A key to the species of Antoonops is provided.